Effect of ligustrazine nanoparticles on Th1/Th2 balance by TLR4/MyD88/NF-κB pathway in rats with postoperative peritoneal adhesion - Yang, Lili (BMC Surg, 2021)
BACKGROUND: Postoperative peritoneal adhesion (PPA) is regarded as fibrous bands connecting both injured abdominal wall and organs or adjacent tissues. It is associated with T helper (Th)1 and Th2 differentiation. However, the critical role of the immunopathogenesis of adhesion formation was precisely unknown. The aim of this study was to investigate the effect of a new agent polylactic acid (PLA) nanoparticles loaded with ligustrazine, that is, ligustrazine nanoparticles (LN) on PPA and identify the potential mechanism. METHODS: Twenty-four Sprague–Dawley rats were randomly divided into the sham, model, LN, and sodium hyaluronate (SH) groups. The structure of LN, including entrapment efficiency (EE) and loading capacity (LC), and in vitro drug release were calculated. Adhesions were scored and the Masson's trichrome staining was used to determine the collagen deposition. The expressions of TLR4, MyD88, and NF-κB were measured by qRT-PCR, immunohistochemistry, and western blot assay. Moreover, Th1-related cytokines (IFN-γ, IL-12), Th2-related cytokines (IL-4, IL-6) in the cecum tissue and serum were conducted by ELISA. RESULTS: LN had good EE, LC, and control-release delivery characters with fairly uniform diameter and spherical morphology. It could effectively prevent adhesion formation after surgery. Besides, it could reduce collagen fibers accumulation, downregulate the expression levels of TLR4, MyD88, and NF-κB, and maintain Th1/Th2 balance. CONCLUSIONS: Ligustrazine nanoparticles had effective effects on Th1/Th2 balance by regulating TLR4/MyD88/NF-κB pathway in PPA rats. It may be served as a promising therapy on postoperative adhesion formation.